Palaeo-sea-level and palaeo-ice-sheet databases: Problems, strategies, and perspectives - Dusterhus A.; Rovere A.; Carlson A. E.; Horton B. P.; Klemann V.; Tarasov L.; Barlow N. L. M.; Bradwell T.; Clark J.; Dutton A.; Roland Gehrels W.; Hibbert F. D.; et al. (Climate of the Past, 2016)
Sea-level and ice-sheet databases have driven numerous advances in understanding the Earth system. We describe the challenges and offer best strategies that can be adopted to build self-consistent and standardised databases of geological and geochemical information used to archive palaeo-sea-levels and palaeo-ice-sheets. There are three phases in the development of a database: (i) measurement, (ii) interpretation, and (iii) database creation. Measurement should include the objective description of the position and age of a sample, description of associated geological features, and quantification of uncertainties. Interpretation of the sample may have a subjective component, but it should always include uncertainties and alternative or contrasting interpretations, with any exclusion of existing interpretations requiring a full justification. During the creation of a database, an approach based on accessibility, transparency, trust, availability, continuity, completeness, and communication of content (ATTAC3) must be adopted. It is essential to consider the community that creates and benefits from a database. We conclude that funding agencies should not only consider the creation of original data in specific research-question-oriented projects, but also include the possibility of using part of the funding for IT-related and database creation tasks, which are essential to guarantee accessibility and maintenance of the collected data.